2023
DOI: 10.1021/acs.macromol.3c00109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Heteroatoms on Mobility–Stretchability Properties of n-Type Semiconducting Polymers with Conjugation Break Spacers

Abstract: The development of stretchable semiconducting polymers through statistical terpolymerization with conjugation break spacers (CBSs) has gained much attention. In this study, we systematically investigated the effects of incorporating CBSs with thioether units into naphthalenediimide (NDI)-based n-type semiconducting polymers on their semiconductivity and stretchability compared to polymers with the corresponding alkyl- and ether-based CBSs. Indeed, six NDI-based semiconducting polymers with CBSs composed of di­… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Therefore, in our previous studies, this method was extended to n -type polymers, and we evaluated the correlation between the chemical structure of CBSs and the properties of the resulting polymers. We successfully synthesized n -type semiconducting polymers with functionalized/branched CBSs and found that the planarity and steric bulkiness of CBSs affect the mechanical and charge transport properties of polymers. , Recently, the effects of incorporating CBSs with thioether units into NDI-based n -type semiconducting polymers on the mobility–stretchability properties were studied and compared with those of polymers with the corresponding alkyl- and ether-based CBSs . This study reports that incorporating heteroatoms into CBSs significantly affects the morphology and stretchability of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in our previous studies, this method was extended to n -type polymers, and we evaluated the correlation between the chemical structure of CBSs and the properties of the resulting polymers. We successfully synthesized n -type semiconducting polymers with functionalized/branched CBSs and found that the planarity and steric bulkiness of CBSs affect the mechanical and charge transport properties of polymers. , Recently, the effects of incorporating CBSs with thioether units into NDI-based n -type semiconducting polymers on the mobility–stretchability properties were studied and compared with those of polymers with the corresponding alkyl- and ether-based CBSs . This study reports that incorporating heteroatoms into CBSs significantly affects the morphology and stretchability of conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…To develop next-generation stretchable electronic devices, improving the efficiency of complementary n -type semiconductor polymers is essential. In the past few years, several molecular designs for intrinsically stretchable n -type semiconducting polymers have been proposed, and their mobility–stretchability properties have been evaluated. , For example, regioregular n -type polymers containing a novel acceptor monomer, thienylvinyl-1,1-dicyanomethylene-3-indanone (TIC), have exhibited superior electron mobility, exceeding 1 cm 2 V –1 s –1 , and these polymers can maintain up to 95% of their mobility even under 100% strain . Block copolymerization of elastomeric materials with low glass-transition temperatures ( T g ), such as polydimethylsiloxane (PDMS; −135 °C) and polyisobutylene (PIB; −73 °C), with naphthalenediimide (NDI)-based n -type semiconducting polymers has also been investigated. , These approaches impart stretchability to the polymer via main-chain modification, considerably affecting the properties of polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N-type (electron-transporting) conjugated polymers are essential components in diverse organic optoelectronic device technologies such as all-polymer solar cells (APSCs), thermoelectric generators, n-type organic field-effect transistors (OFETs), , and others, , and for these reasons have been extensively studied over the past two decades. N-type polymers based on the naphthalene diimide ( NDI ) acceptor unit are among the most investigated with poly­[ N , N ′-bis­(2-octyldodecyl)-naphthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl]- alt -5,5′-(2,2′-bithiophene) ( PNDITh2 or N2200 ) being the most prominent example, exhibiting an impressive electron mobility surpassing 6 cm 2 /(V s), low energetic disorder, and enabling APSC power conversion efficiencies >10%. Since N2200 exhibits an important optoelectronic performance, several NDI -based donor–acceptor (D-A) copolymers with regioregular (RR) and regioirregular (RI) architectures have been developed. However, NDI polymers achieved via/comprising an asymmetric NDI building block have not been reported to date due to limited synthetic protocols . Asymmetric structures generate local dipoles that can enhance interactions between neighboring molecules, hence favoring charge transport as well as photovoltaic performance for several organic semiconductors. Conventional Stille polycondensation reactions using dibrominated NDI building blocks and bis­(trialkylstannyl) aryl units as the starting materials have been the primary synthetic method for preparing NDI polymers; however, this approach is not particularly sustainable and using two symmetric building blocks only generates symmetric NDI polymers. , Kiriy and co-workers have developed an effective alternative polymerization protocol in which 2,6-di­(bromoaryl) substituted NDI units (Br-Het- NDI -Het-Br) are polymerized using activated zinc, which avoids the use of toxic stannanes.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various strategies for manipulating thin film thermomechanical properties, the introduction of regiorandom nonconjugated linkers, so-called “conjugation breaking spacers” (CBS), directly within the backbone of semiconducting polymers has become a design strategy of interest for tuning solubility, solid-state nanostructure and thermal transitions, all of which contribute to thin film characteristics and properties. , The primary advantage of introducing CBS within the conjugated backbone is its impact on the material’s mechanical properties, as the spacers yield high degrees of conformational and energetic disorder in the polymer chains. In previous reports, CBS designs from simple flexible alkyl chain linkers have allowed for conjugated polymers to be processed in new ways such as melt processing. , The incorporation of hydrogen bonding moieties and heteroatoms in CBS has also enabled the design and synthesis of more mechanically robust materials with self-healing properties and increased tolerance to strain deformation. , While the incorporation of CBS within the backbone of conjugated polymers has been shown to reduce the effective charge carrier mobility of materials, the incorporation of low molar percentage ratios (<30%) of CBS can still lead to good charge transport in electronic devices while allowing for an easier processing by solution deposition in common organic solvents. , Furthermore, previous reports have shown that the careful synthetic design of CBS can drive the self-assembly of polymer chains in the solid state and can enhance charge transport characteristics, indicating that the relationship between CBS linkers and charge transport is complex. …”
Section: Introductionmentioning
confidence: 99%